Long-term effects of anti-N-methyl-d-aspartate receptor encephalitis on quality of life - Hirose, Satoshi; Hara, Makoto; Yokota, Yuki; Nakajima, Hideto (Frontiers in Neurology, 2023)
Background: Patients with anti-N-methyl-D-aspartate receptor encephalitis (NMDARE) usually achieve neurologically favorable outcomes in the post-acute-phase. Even when motor function recovers, many patients experience numerous non-motor sequelae and cannot resume their pre-NMDARE lives even years later. Additionally, the needs of patients with NMDARE may impose a severe caregiver burden. Unfortunately, few studies have comprehensively examined patients recovering from NMDARE. We investigated the long-term effects of NMDARE on patients' quality of life (QOL). Methods: Data collected via structured self-reported questionnaires included clinical features, long-term outcomes, and QOL. These questionnaires were administered to adult members of the Japanese Anti-NMDARE Patients' Association. We used the NeuroQOL battery to assess QOL in physical, mental, and social domains. Raw NeuroQOL scores were converted to T-scores for comparison with controls. Results: Twenty-two patients completed the questionnaire. The median interval between disease onset and questionnaire response was 78 months. Forty-six percent of patients reported persistent sequelae, with only 73% able to resume prior work/school activities. Although patients’ Global QOL was similar to controls, patients with NMDARE had significantly worse social QOL. Patients with worse social QOL had more-frequent sequelae than those with better social QOL. Furthermore, patients with persistent sequelae had significantly worse Global QOL than those without sequelae and controls. Conclusions: Patients with NMDARE had worse social QOL than controls. Given the adverse effects of disease sequelae on QOL, treatment strategies that minimize sequelae during the acute-phase may improve patients' QOL, even years post-disease onset.